2007
DOI: 10.1111/j.1600-0854.2007.00657.x
|View full text |Cite
|
Sign up to set email alerts
|

The Single Dynamin Family Protein in the Primitive Protozoan Giardia lamblia Is Essential for Stage Conversion and Endocytic Transport

Abstract: Dynamins are universally conserved large guanosine triphosphatases, which function as mechanoenzymes in membrane scission. The primitive protozoan Giardia lamblia has a single dynamin-related protein (GlDRP) with an unusual domain structure. Giardia lacks a Golgi apparatus but generates transient Golgi-like delay compartments dubbed encystation-specific vesicles (ESVs), which serve to accumulate and mature cyst wall proteins during differentiation to infectious cyst forms. Here, we analyze the function of GlDR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
118
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(131 citation statements)
references
References 55 publications
12
118
1
Order By: Relevance
“…We have shown that giActin is associated with the Golgi-like ESVs (Fig. 2D), where the trafficking of CWP is thought to involve clathrin and dynamin (37). To test the role of giActin in CWP trafficking, we encysted actin knockdown cultures.…”
Section: Resultsmentioning
confidence: 99%
“…We have shown that giActin is associated with the Golgi-like ESVs (Fig. 2D), where the trafficking of CWP is thought to involve clathrin and dynamin (37). To test the role of giActin in CWP trafficking, we encysted actin knockdown cultures.…”
Section: Resultsmentioning
confidence: 99%
“…There is partial although not conclusive experimental support for this idea. The class A dynamin of the excavate Trypanosoma brucei localizes to mitochondria (25) but appears to be required for mitochondrial fission as well as endocytosis (26); that of the amitochondriate excavate Giardia lamblia colocalizes with clathrin-coated vesicles (27). The class A dynamin of the red alga Cyanidioschyzon merolae has a punctate distribution on the cell surface between mitochondrial division events, suggesting it might also participate in vesicle scission (28,29).…”
Section: Extant Eukaryotes Have Separate Mitochondrial and Vesicle Scmentioning
confidence: 99%
“…In addition, their potential role in endocytosis was demonstrated by the uptake of exogenous ferritin and Lucifer yellow (Bockman and Winborn, 1968;Lanfredi-Rangel et al, 1998). Pulse-chase experiments with horseradish peroxidase and fluorescent dextran showed an early and persistent labeling of the PVs, suggesting that there is no distinction between early and late endocytic vesicles in Giardia, in contrast to what occurs in higher eukaryotes (LanfrediRangel et al, 1998;Gaechter et al, 2008). Analysis of fluid-phase endocytosis demonstrated that there is no lateral exchange of fluid phase markers between individual PVs (Gaechter et al, 2008).…”
Section: The Endosomal/lysosomal System Of Giardiamentioning
confidence: 99%
“…Pulse-chase experiments with horseradish peroxidase and fluorescent dextran showed an early and persistent labeling of the PVs, suggesting that there is no distinction between early and late endocytic vesicles in Giardia, in contrast to what occurs in higher eukaryotes (LanfrediRangel et al, 1998;Gaechter et al, 2008). Analysis of fluid-phase endocytosis demonstrated that there is no lateral exchange of fluid phase markers between individual PVs (Gaechter et al, 2008). It was observed that, after internalization, some fluid-phase markers translocated rapidly to the ER or to an associated membrane compartment termed the tubulo-vesicular network (TVN) (Abodeely et al, 2009).…”
Section: The Endosomal/lysosomal System Of Giardiamentioning
confidence: 99%
See 1 more Smart Citation